Beyond raw: Investigating alternative preparation methods as a tool to increase acceptance of oysters in Sweden - Elena Costa; Anna-Lisa Wrange; Elizabeth S. Collier; Jun Niimi; Åsa Strand (Future Foods, 2023)
The role of seafood in supporting transitions towards more sustainable and healthier diets is often overlooked. Oysters, for example, are a nutrient dense aquatic food whose production requires no feed, freshwater, or land use. However, oyster consumption in Sweden is limited, possibly in part due to being traditionally served raw. This study investigated consumer acceptance of oysters when cooked and prepared to resemble familiar foods and examined whether food neophobia (FN) was related to liking. Four oyster-based samples (raw oyster, oyster crepe, oyster burger, and oyster soup) were evaluated in an ecologically valid setting. Participants (N=102; convenience sampling) rated the samples in terms of hedonics (expected liking and liking after tasting), described which aspects of the samples were liked/disliked, and reported the contexts in which oyster consumption is perceived as appropriate. The findings suggest that FN was negatively associated with expected liking of raw oysters, but not with expected liking for cooked oyster-based products that were cooked to resemble familiar foods. On the other hand, familiarity with oysters was positively associated with expected liking of raw oysters. This suggests that expanding oyster preparations beyond its traditional raw format could be a valuable strategy to promote oyster consumption in Sweden.